2007
DOI: 10.1097/mlg.0b013e3180600a16
|View full text |Cite
|
Sign up to set email alerts
|

Pain Treatment and Recovery After Endoscopic Sinus Surgery

Abstract: The present study suggests that patients recover in 9 to 10 days after ESS when provided with appropriate pain management. Our data indicate that by prescribing scheduled acetaminophen, postoperative pain after ESS can be controlled effectively without the need for opioid analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
(54 reference statements)
2
33
0
Order By: Relevance
“…These inflammation‐related symptoms generally last 1 week or less. Kemppainen et al reported that patient discharge and return to normal daily activities is approximately between 8 and 10 days after nasal surgery . Similarly to their study, the VAS and NOSE scores of our patients were highest on postoperative day 5 (3 days after nasal splints were removed) and returned to normal on day 12 (10 days after nasal splints were removed).…”
Section: Discussionsupporting
confidence: 84%
“…These inflammation‐related symptoms generally last 1 week or less. Kemppainen et al reported that patient discharge and return to normal daily activities is approximately between 8 and 10 days after nasal surgery . Similarly to their study, the VAS and NOSE scores of our patients were highest on postoperative day 5 (3 days after nasal splints were removed) and returned to normal on day 12 (10 days after nasal splints were removed).…”
Section: Discussionsupporting
confidence: 84%
“…18 Previous research has also suggested the efficacy of scheduled acetaminophen alone in achieving return to normal daily activities when compared with an as-needed group. 19 However, 1 patient in the scheduled group and 5 in the asneeded group indicated insufficient analgesia with the nonopioid regimen. Similarly, in the study conducted by Wise et al, 2 patients used over 30 tablets over the study period.…”
Section: Discussionmentioning
confidence: 98%
“…The American Society of Anesthesiologists and the American Pain Society recommend using nonopioid analgesics postoperatively, when not contraindicated . Scheduled acetaminophen, as opposed to as‐needed administration, can provide effective pain control and reduce opioid requirements after ESS . In addition, nonsteroidal anti‐inflammatory drugs (NSAIDs) are a safe and effective alternative to opioids for patients without contraindications.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Scheduled acetaminophen, as opposed to as-needed administration, can provide effective pain control and reduce opioid requirements after ESS. 20,21 In addition, nonsteroidal anti-inflammatory drugs (NSAIDs) are a safe and effective alternative to opioids for patients without contraindications. The evidence supporting NSAID use for postoperative analgesia after ESS has an A grade, pursuant to the Grading of Recommendations Assessment, Development and Evaluation approach, and NSAIDs may reduce postoperative opioid consumption.…”
Section: Discussionmentioning
confidence: 99%